THE EFFECTS OF PERCEPTION ON LECTURE’S PEDAGOGIC COMPETENCEAND ENVIRONMENT TOWARDS STUDENT’S SPEAKING SKILL OF ENGLISH - Isnaeni, Resti (CV. Pena Persada, 2019)
In advancing education in our country, lecturers and teachers are very important role in developing the potential of students possessed. The future of the nation is in the hands of educators through the national education process. This effort is able to improve lecturer competency education which includes pedagogical, personal, social, and professional competencies. Improving the quality of lecturers can also be done in various ways including lecturer academic qualifications, training, certification testing, and providing classroom action research. In addition to the influence of the competence of lecturers, the environment is also a place for the occurrence of the interaction process between one person and another which greatly influences student learning abilities. The environment can directly affect a person's attitude, behavior, and personality. For that the environment that surrounds us and affects the learning process. called the learning environment. The environment also an important role in learning English, especially speaking skills. The role of the environment here is as a place where students can express and apply the use of English that has been learned in communication in daily life. The environment is very influential on student motivation in improving their ability to speak English.